Influence of sulfur doping on the electrical and thermal transport properties of FeTe1-xSx superconductors. (December 2018) - Lodhi, Pavitra Devi; Kaurav, Netram; Huang, R.Y.; Kuo, Y.K.
Abstract: In this study, we determined the structural, electrical, and thermal transport properties of the FeTe1− x S x system, where x = 0.0, 0.1, 0.2, and 0.3. The samples were synthesized using a standard solid-state reaction route via vacuum encapsulation and characterized by X-ray diffraction, which indicated a tetragonal phase with the P4/nmm space group. The parent compound FeTe exhibited an anomaly according to the resistivity measurements at around 67 K due to structural change. The S-substituted samples exhibited negative dependence on the temperature at an electrical resistivity above 10 K, and quantitative analysis indicated that the variable range hopping mechanism governs electrical conduction in the FeTe1− x S x system. In the low-temperature regime, the Seebeck coefficient, S ( T ), had an anomalous dip feature with crossover of the sign, which can be understood based on the phonon drag contributions and the multiband picture, respectively. The lattice phonons made major contributions to the measured thermal conductivity, κ ( T ). In addition, we observed a reduction in the height of the low-temperature phonon peak with κ due to the substitution of S for Te, thereby indicating strong enhancement of the disorder-induced phonon scattering. Moreover, a positive d κ /d T was observed in the normal state, which might be related to local anharmonic lattice distortions. Overall, based on our analyses, we conclude that phonons play important roles in the transport properties of FeTe1- x S x superconductors. Highlights: Structural, electrical, and thermal features of FeTe1− x S x ( x = 0.0, 0.1, 0.2, 0.3). Parent FeTe compound exhibited anomalous resistivity at ca 67 K. Electrical resistivity above 10 K negatively dependent on temperature with S. Variable range hopping mechanism governs electrical conduction in FeTe1− x S x . Positive derivative in thermal conductivity due to anharmonic lattice distortion.